DUE TO THE LEGAL TERMINATION OF MOTOR VEHICLE INSURANCE AGAINST THE INSURANCED HIMALAYA INSURANCE COMPANY IN BENGKULU CITY - Amelia Nindi Astuti (Jurnal Multidisiplin Sahombu, 2021)
The purpose of this study is to examine the basis for termination of coverage at the Himalayan Insurance Company for the coverage of four-wheeled motor vehicles (cars) against the Insured, and the rights of the Insured in terminating the coverage of four-wheeled motor vehicles (cars) carried out by Himalayan Insurance Companies. The results showed that (1) Central Hilmalaya Insurance with the Consumer Finance Company PT. Oto Multiartha Pusat cooperates in insuring motor vehicles whose four-wheeled motor vehicles (cars) are financed by the Consumer Finance Company PT. Oto Multiartha as a Financing Institution. Hilmalaya Insurance Company in Bengkulu City as the Insurer and the Consumer Finance Company PT. Oto Multiartha Bengkulu Branch as the Insured Party, both parties are bound by a Motor Vehicle insurance agreement. This Insurance Agreement is executed by the Consumer Finance Company PT. Oto Multiartha as the Insured can transfer the risk of the four-wheeled motorized vehicle (car) it finances if the Consumer has not paid off the credit. (2) The Insured's right to terminate the insurance for motor vehicles (cars) carried out by Himalaya Insurance Company against the Consumer Finance Company PT. Oto Multiartha must comply with the agreement made between the two parties and not conflict with the Standard Motor Vehicle Insurance Policy. There are two types of rights obtained by the Insured, namely: a. The insured is entitled to receive the remaining premium by means of prorated calculation by the insurer, b. The Insured is still entitled to transfer the risk of the object of the motor vehicle (car) to the Insurance company as long as the period has not expired. The insured only gets one of the 2 kinds of rights above